Pengetahuan Pasien Tentang Penyakit TB Paru Di Balai Besar Kesehatan Paru Masyarakat Makassar - Nurhaedah Nurhaedah; Herman Herman (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Pulmonary TB is a simple disease that is easy to treat and its main management is to treat the symptoms only. Limited knowledge about pulmonary TB makes this disease often not handled properly. Method: This type of descriptive analytic research, where the method used in data collection by distributing questionnaires to respondents. The population in this study were all patients who came for treatment. Research data processing is carried out through the following stages: selection, editing, coding, tabulation. Analysis of the data used in this research is descriptive analysis. Results: showed good knowledge about the way of transmission, regularity of taking medication and complications of pulmonary TB as many as 10 people (33%) and those who lack knowledge about the mode of transmission, regularity of taking drugs and complications of pulmonary TB as many as 20 people (67%). Most of them have less knowledge about the mode of transmission, regular medication and complications of pulmonary TB disease. This shows that the knowledge possessed by patients with pulmonary TB is not so broad about the complications of pulmonary TB disease. Providing constructive motivation and encouragement to pulmonary TB patients and providing effective health education to pulmonary TB patients when seeking treatment